Availability of Science Laboratory in Schools at the Secondary Level - Pareek, Ram Babu (SCHOOL SCIENCE, 2017)
The study determined the availability of science laboratories for teaching learning of science at the secondary level in selected secondary schools of Rajasthan. The research design adopted for the study was stratified random sampling— out of 33 districts of Rajasthan— three districts, namely, Jaipur, Nagaur and Ajmer were randomly selected. Then seven government secondary schools from each district were selected. Three instruments, which were prepared by a team of faculty members and RMSA cell members were used for the collection of data for the study. They are questionnaires for principal/headmaster of the school, teachers and students focus group discussion. The data were collected by visiting the concerned school personally by faculty members. The study showed that laboratory facilities are highly inadequate, far below the expectation and in most of the schools experiments are not conducted. It is, therefore, recommended that government should include practicals in science as a part of assessment and take immediate steps to set up science laboratories across the state for effective teaching and learning of science. It is also suggested to make the science teachers more resourceful in providing alternative material for science teaching and learning so that learners learn by doing and develop thinking skills and attempt at innovations.